Bistable Joints Enable the Morphing of Hydrogel Sheets with Multistable Configurations. Issue 15 (2nd March 2023) - Li, Chen Yu; Jiao, Dejin; Hao, Xing Peng; Hong, Wei; Zheng, Qiang; Wu, Zi Liang
Abstract: Joints, as a flexing element to connect different parts, are widespread in natural systems. Various joints exist in the body and play crucial roles to execute gestures and gaits. These scenarios have inspired the design of mechanical joints with passive, hard materials, which usually need an external power supply to drive the transformations. The incorporation of soft and active joints provides a modular strategy to devise soft actuators and robots. However, transformations of responsive joints under external stimuli are usually in uni‐mode with a pre‐determined direction. Here, hydrogel joints capable of folding and twisting transformation in bi‐mode are reported, which enable the composite hydrogel to form multiple configurations under constant conditions. These joints have an in‐plane gradient structure and comprise stiff, passive gel as the frame and soft, active gel as the actuating unit. Under external stimuli, the response mismatch between different gels leads to out‐of‐plane folding or twisting deformation with the feature of bistability. These joints can be modularly integrated with other gels to afford complex deformations and multistable configurations. This approach favors selective control of hydrogel's architectures and versatile design of hydrogel devices, as demonstrated by proof‐of‐concept examples. It shall also merit the development of metamaterials, soft actuators, and robots, etc. Abstract : Active joints are designed by using a stiff gel as a frame and a responsive gel as an actuating unit. The response mismatch in the joint with in‐plane gradient leads to folding or twisting with the feature of bistability. Integration of multiple joints into one hydrogel enables the formation of multistable configurations that facilitate designs of hydrogel devices with versatile functions.